Complementarity between labor and energy: A firm-level analysis - Lucas Bretschger; Ara Jo (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
This paper adds a fresh angle to the on-going debate on the potential negative employment effect of environmental policy by bringing to the fore a key factor that directly regulates its magnitude: the elasticity of substitution between labor and energy. Using firm-level data from the French manufacturing sector, we provide rigorous micro estimates of this parameter that point to strong complementarity between labor and energy. We then provide clear evidence for the empirical, as well as theoretical, relevance of the elasticity of substitution in understanding the effect of environmental policies on employment.
Keywords: Q40; Q54; Q55; O33; 330; market-based regulation; employment; elasticity of substitution